Progress in extracellular vesicle biology and their application in cancer medicine. (4th March 2020) - Srivastava, Akhil; Amreddy, Narsireddy; Pareek, Vipul; Chinnappan, Mahendran; Ahmed, Rebaz; Mehta, Meghna; Razaq, Mohammad; Munshi, Anupama; Ramesh, Rajagopal
Abstract: Under the broader category of extracellular vesicles (EVs), exosomes are now well recognized for their contribution and potential for biomedical research. During the last ten years, numerous technologies for purification and characterization of EVs have been developed. This enhanced knowledge has resulted in the development of novel applications of EVs. This review is an attempt to capture the exponential growth observed in EV science in the last decade and discuss the future potential to improve our understanding of EVs, develop technologies to overcome current limitations, and advance their utility for human benefit, especially in cancer medicine. This article is categorized under: Therapeutic Approaches and Drug Discovery > Emerging Technologies Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Abstract : Landscape of extracellular vesicles in biology and disease.